Association between neonatal morbidities and head growth from birth until discharge in very‐low‐birthweight infants born preterm: a population‐based study. (23rd May 2016) - Regev, Rivka H; Arnon, Shmuel; Litmanovitz, Ita; Bauer‐Rusek, Sofia; Boyko, Valentina; Lerner‐Geva, Liat; Reichman, Brian
Abstract : Aim: To evaluate the possible association between major neonatal morbidities and poor head growth from birth to discharge home in very‐low‐birthweight (VLBW) infants born preterm. Method: Population‐based observational study comprising 12 992 infants (6340 male, 6652 female) of 24 to 32 weeks' gestation, and birthweight ≤1500g. Severe head growth failure (HGF) was defined as a decrease in head circumference z‐score >2 z‐scores, and moderate HGF as a decrease of 1 to 2 z‐scores. Multinomial logistic regression analysis was applied to determine morbidities associated with HGF. Results: Severe HGF occurred in 4.5% and moderate HGF in 20.9% of infants. Each unit increase in head circumference z‐score at birth was associated with increased odds for severe and moderate HGF (odds ratios [OR] 5.29, 95% confidence intervals [CI] 4.67–6.00, and OR 2.38, 95% CI 2.23–2.54 respectively). Both severe and moderate HGF were associated with respiratory distress syndrome (OR 2.03, 95% CI 1.58–2.62, and OR 1.66, 95% CI 1.48–1.85 respectively); bronchopulmonary dysplasia (OR 3.38, 95% CI 2.33–4.91, and OR 1.87, 95% CI 1.52–2.30 respectively); necrotizing enterocolitis (OR 2.89, 95% CI 2.04–4.09, and OR 1.72, 95% CI 1.38–2.16 respectively), and sepsis (OR 2.06, 95% CI 1.69–2.50, and OR 1.38, 95% CI 1.24–1.53 respectively). Interpretation: Major neonatal morbidities were associated with HGF in VLBW infants born preterm. Identification of whether this is a direct effect of these morbidities or mediated through nutritional or growth factors may enable interventions to improve postnatal head growth of infants born preterm. What this paper adds: Postnatal head growth failure (HGF) occurred in 25% of very‐low‐birthweight infants born preterm. Increasing head circumference at birth was associated with an increased risk for severe HGF. Acute neonatal morbidities were associated with 2‐ to 3‐fold greater risk for severe HGF. Rates of severe and moderate HGF were lower in small for gestational age infants.